Exploring the factors associated with depressive symptoms and understanding stigma associated with living in a care home among older adults residing in care homes in Thailand - Tosangwarn, Suhathai (2018)
Background: Thai culture venerates caring for elders, thus care homes are stigmatised as the domain of poor older adults with no family. This impacts negatively on the psychological wellbeing of older residents and the high prevalence of depression reported among them. However, little is understood about the key factors influencing the depressive symptoms and how such stigma is experienced among care home residents. This study explored factors associated with depressive symptoms, internalised stigma, self-esteem, social support and coping strategies among residents from the perspectives of residents and staff. Methods: Mixed methods research (convergent parallel design) was conducted in two care homes in northeast Thailand using a cross-sectional questionnaire, in-depth interview and non-participant observation. A cross-sectional questionnaire study was conducted with 128 older care home residents (with a response rate of 98.46%) using the 15-Item Thai Geriatric Depression Scale, Internalised Stigma of Living in a Care Home Scale, Thai Version of Rosenberg Self-Esteem Scale, Thai Version of Multidimensional Scale of Perceived Social Support and a Coping Strategies Inventory Short Form. Qualitative interviews were conducted with 30 older residents and 20 care home staff purposively sampled from both care homes. Non-participant observation was conducted in various public spaces of the care homes in both care homes for one month. Quantitative data was analysed using the Statistical Package for Social Science (SPSS) IBM PASW Version 22.0 for Windows. Thematic analysis was used to analyse the qualitative data.